Sistem Among dalam Penerapan Nilai-nilai Luhur Pendidikan Karakter Ki Hadjar Dewantara - Fressi Apriliyanti; Fattah Hanurawan; Ahmad Yusuf Sobri (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this study was to describe the wholeness of the Among System in the application of the noble values in the character education of Ki Hadjar Dewantara. The case study qualitative research data collected using in-depth interviews, observations and study documents. The data analysis technique in this study was thematic analysis and validated by source triangulation and method triangulation The results showed that the Among System demonstrated the application of the noble values of the education of Ki Hadjar Dewantara's characters in TK Taman Indria Malang City including the application of ing ngarso sung tulodho, ing madyo mangun karso, and Tut Wuri Handayani. The methods used in implementing of the Among System in TK Taman Indria contained methods of habit, exemplary, storytelling and conversing. The characters that appeared from the implementation of the Among System including politeness, responsibility, disciplines, orderly and accepting rules. Various strategies were used in the preservation of the noble values of the character education of Ki Hadjar Dewantara and were used in dealing with the obstacles in preserving the noble values of the education of Ki Hadjar Dewantara's characters in TK Taman Indria.Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan secara menyeluruh mengenai Sistem Among dalam penerapan nilai-nilai luhur pendidikan karakter Ki Hadjar Dewantara. Rancangan penelitian yang digunakan adalah penelitian kualitatif studi kasus. Alat pengumpul data dalam penelitian ini adalah wawancara mendalam, observasi dan studi dokumen. Teknik analisis data dalam penelitian ini adalah tematik analisis. Derajat keterpercayaan dalam penelitian ini dicapai dengan menggunakan triangulasi sumber dan triangulasi metode. Hasil penelitian menunjukkan bahwa Sistem Among dalam penerapan nilai nilai luhur pendidikan karakter Ki Hadjar Dewantara di TK Taman Indria Kota Malang meliputi adanya Penerapan Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso, Tut Wuri Handayani. Metode dalam penerapan Sistem Among di TK Taman Indria antara lain metode pembiasaan, keteladanan, bercerita dan  bercakap-cakap. Ditemukan berbagai strategi pelestarian nilai-nilai luhur pendidikan karakter Ki Hadjar Dewantara serta hambatan dalam pelestarian nilai-nilai luhur pendidikan karakter Ki Hadjar Dewantara di TK Taman Indria.